Audit Problems Encountered in Small Business Engagements (Book). - Martin, Jimmy W.; Hendrickson, Harvey S. (The Accounting Review, 1985)
Abstract Reviews the book "Audit Problems Encountered in Small Business Engagements," by D.D. Raiborn.